Effectiveness of topical application of honey in the management of radiation induced oral mucositis - Karthikeya Patil; C J Sanjay; S Viveka; Nagabhushana Doggalli; R Aishwarya (Wolters Kluwer Medknow Publications, 2022)
Background and Objective: Most patients with oral cancer receive chemoradiotherapy with or without surgery for treatment and develop oral mucositis, a debilitating adverse. Currently, there is no standard regimen for the management of radiation-induced mucositis. This study aims to evaluate the effect of honey on radiation-induced mucositis. Methods: The study consisted of 204 subjects of both genders, diagnosed and treated by radiotherapy for head and neck carcinoma and who had developed oral mucositis. The control group (n = 102) received 0.9% normal saline while the interventional group (n = 102) received honey as a topical application. Both groups were evaluated by the World Health Organization oral mucositis assessment scale at baseline (I visit) and four follow-up visits. Results: A decrease in the progression of the lesion and symptomatic relief were found in the interventional group. There was neither symptomatic relief nor a decrease in mucositis grade in the control group. Conclusion: Within the limits of this study, the results showed that the topical application of honey could be used to alleviate the symptoms in the management of radiation mucositis as it is easily available, simple, and economical.